The equivalent algebraic monomial expression of the expression given as (-8a^5b)(3ab^4) is -24a^6b^5
<h3>How to determine an equivalent algebraic monomial expression?</h3>
The expression is given as:
(-8a^5b)(3ab^4)
Multiply -8 and 3
So, we have:
(-8a^5b)(3ab^4) = (-24a^5b)(ab^4)
Multiply a^5 and a (a^5 * a = a^6)
So, we have:
(-8a^5b)(3ab^4) = (-24a^6b)(b^4)
Multiply b and b^4
So, we have:
(-8a^5b)(3ab^4) = -24a^6b^5
Hence, the equivalent algebraic monomial expression of the expression given as (-8a^5b)(3ab^4) is -24a^6b^5
Read more about expressions at:
brainly.com/question/723406
#SPJ1
A circle has infinit lines of symmetry. They pass through the centre of the circle and are the circle's diameter.
Hope this helps! (:
Y= -9x
---
8
hope this helps
<span><span>
</span></span>
When it says 7/10, it actually means 70%, so you have to find 70% of 120.
<span>
70 % of 120
= 70% x 120
= (70/100) x 120
= (8400/100)
= 84
Answer: 84</span>
Answer:
1/3x
Step-by-step explanation:
Subtract x by x and y by y to find the distance/difference
36 163
24, 127
= 12/36 = rise/run
Now reduce to find the slope, reduce until you can't anymore.
12/36
6/18
3/9
1/3 (that's your slope)